(untitled) (Biological Sciences - PJSIR, 2001)
One hundred and five soybean germplasms of exotic and national origin were evaluated for their reaction to anthracnose under field condition in Bangladesh. In the field 36 materials were found to be free from infection of C. truncatum (highly resistant) while 19, 37, 3, 5 and 5 germplasms were graded as resistant, moderately resistant, moderately susceptible, susceptible and highly susceptible, respectively. Percentage of seed-borne infection by Colletotrichum truncatum varied from one germ plasm to another. In total 43 gennplasms were completely free from seed-borne infection, whereas upto 5% infection was recorded in 25 samples, 6-30% in 32 samples and 31-36% infection was found in five samples.